2019
DOI: 10.3389/fphar.2019.00537
|View full text |Cite
|
Sign up to set email alerts
|

The Glp-1 Analog Liraglutide Protects Against Angiotensin II and Pressure Overload-Induced Cardiac Hypertrophy via PI3K/Akt1 and AMPKa Signaling

Abstract: The Glp-1 analog, liraglutide (Lir), has been shown to reduce infarct size and improve cardiac function after myocardial ischemia in rodents with or without diabetes. However, the effect of Lir on angiotensin II (AngII) and pressure overload induced cardiac hypertrophy in nondiabetic mice and the underlying mechanisms are unclear. The aim of this study was to investigate the effect of Lir on cardiac hypertrophy induced by AngII infusion and pressure overload and to explore its possible mechanism. Mice were sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…and AKT2, but not AKT3 were reported to inhibit fibrogenesis in hepatocytes and HSC [39]. Besides, previous studies had revealed that the PI3K/AKT signaling pathway was associated with hypertrophy and fibrosis in different tissues such as cardiac hypertrophy [40] and liver fibrosis [18]. Moreover, our data also found that AA treatment upregulated the phosphorylation of AMPK.…”
Section: Discussionsupporting
confidence: 61%
“…and AKT2, but not AKT3 were reported to inhibit fibrogenesis in hepatocytes and HSC [39]. Besides, previous studies had revealed that the PI3K/AKT signaling pathway was associated with hypertrophy and fibrosis in different tissues such as cardiac hypertrophy [40] and liver fibrosis [18]. Moreover, our data also found that AA treatment upregulated the phosphorylation of AMPK.…”
Section: Discussionsupporting
confidence: 61%
“…However, the mechanism by which GLP-1 agonists exert their cardiovascular protective action, especially to improve ventricular remodeling, is still unclear. It was reported that liraglutide, one kind of GLP-1 agonist, inhibited angiotensin II and pressure overload-induced cardiac remodeling by regulating PI3K/Akt1 and AMPKα signaling [63]. Wang et al [64] also found that the cardiac protection of GLP-1 agonists might be dependent on inhibition of oxidative stress through the mammalian target of rapamycin complex 1/p70 ribosomal protein S6 kinase pathway.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 Liraglutide also inhibits cardiac remodeling via regulating PI3K/Akt1 and AMPKα signaling. 45 Thus, the effects of liraglutide on myocardial fibrosis are multifactorial and partially related to activation of adenosine 5‘-monophosphate (AMP)-activated protein kinase-α (AMPKα) signaling.…”
Section: Discussionmentioning
confidence: 99%